Co inoculation of AM fungi Glomus macrocarpum and Acaulospora laevis and Bacillus megaterium var phosphaticum on the growth and nutrient contents of Solanum xanthocarpum Schrad and Wendl - R T S, Nandini (International Journal of Pharmaceutical & Biological Archive, 2012)
Co inoculation of AM fungi Glomus macrocarpum and Acaulospora laevis and Bacillus megaterium var phosphaticum on the growth and nutrient contents of Solanum xanthocarpum Schrad and Wendl